Case Report: High-Calorie Glucose Infusion and Tight Glycemic Control in Ameliorating Refractory Acidosis of Empagliflozin-Induced Euglycemic Diabetic Ketoacidosis - Wan Azman, Siti Sanaa; Sukor, Norlela; Abu Shamsi, Muhammad Yusuf; Ismail, Ilham; Kamaruddin, Nor Azmi (Frontiers in Endocrinology, 2022)
The current widespread use of SGLT2-inhibitors has triggered an increase in the reported cases of euglycaemic diabetic ketoacidosis (EDKA), often characterised by a protracted metabolic acidosis which is resistant to conventional DKA treatment. We report a case of SGLT2-inhibitor induced EDKA with severe metabolic acidosis intractable to aggressive fluid resuscitation and boluses of bicarbonate infusion. Following the introduction of high calorie glucose infusion coupled with tight glycaemic control the recalcitrant acidosis was successfully corrected. This is the first case report that adopt the above approach representing a paradigm shift in the management of SGLT2-inhibitor induced EDKA.